“Sport can unite people, but not with them, they don't love this country” ethnic prejudice and identity among basketball fans in North Macedonia - Agich, Arin; Váradi, Luca; Dóczi, Tamás (Frontiers in Sports and Active Living, 2025)
This study explores how ethnic identity and intergroup prejudice are shaped, expressed and challenged within basketball fandom in North Macedonia, a multi-ethnic and divided society. While sports fan culture is widely recognized as a platform where group belonging and identity are developed, there is limited qualitative research in the Balkans that examines how these identities intersect with ethnic divisions in everyday fan practices. In particular, this study looks at whether sports can serve as a tool for inclusion and reducing ethnic-based prejudice among fans in post-conflict and multi-ethnic societies. To address this gap, we conducted six focus group discussions with 30 members of ethnic-Macedonian and ethnic-Albanian basketball fan groups. Using thematic analysis, we analyzed (a) how fan identities are shaped by group and ethnic belonging and expressed through group symbols, loyalty, and rituals; (b) how intergroup prejudice and exclusion are expressed through perceptions of rivalry and national representation, and (c) whether extended intergroup contact can reduce prejudice among fans. Our findings reveal that fan identities are intertwined with broader socio-political narratives, and that sporting spaces often reinforce, rather than bridge, symbolic boundaries. In addition, Extended Contact Hypothesis (ECH) remains largely ineffective due to emotional detachment and conditional acceptance of the other. These insights offer further understanding of the role of sports and the limitations of contact-based interventions in divided societies, such as North Macedonia.